Deuterium retention in liquid tin exposed to atomic deuterium flux. (22nd December 2020) - Zaplotnik, Rok; Nemanič, Vincenc; Žumer, Marko; Kovač, Janez; Mozetič, Miran
Abstract: Liquid tin samples at a temperature of 250 °C were exposed to neutral deuterium atoms at a flux of about 10 24 m −2 s −1 . The source of deuterium (D) atoms was the flowing afterglow of a low-pressure deuterium plasma sustained with a microwave discharge in the surfatron mode. The samples were analyzed by thermal desorption spectroscopy and time of flight secondary-ion mass spectrometry. An immeasurably low concentration of deuterium was detected in the pure tin. However, within the native layer of tin oxide, up to 165 ppm D/Sn was absorbed while the sample was exposed to D atoms. The deuterium concentration in the solid samples peaked at the D fluence of about 5 × 10 25 m −2 . At the fluence of several 10 26 m −2 the concentration dropped below the detection limit, which was about 50 ppb D/Sn. The results were explained by the reduction of the oxide film under exposure to D atoms at large fluences. Thus, the retention of hydrogen isotopes in the liquid tin divertor of a fusion reactor is unlikely since the effect of the plasma makes it possible to reduce the tin oxide layer.